Survey to Solutions: A Digital Health Platform to Promote Safe Drug Disposal Practices in India - Ghadge, Mayuri; Yadav, Nikhil; Joshi, Tanmayee (Indian Journal of Pharmacy Practice, 2026)
Background: Improper disposal of unused or expired medicines poses serious risks to both public health and the environment. In India, limited awareness of official guidelines and the absence of systematic collection mechanisms contribute to unsafe practices, such as discarding medicines in household trash. Objectives: This study aimed to assess the knowledge, attitudes, and practices of the public regarding drug disposal in India and to develop a digital platform, PillBin, to promote safe and accessible disposal practices. Materials and Methods: A cross-sectional survey was conducted with 383 participants from varied professional backgrounds between December 2024 and January 2025. A structured questionnaire was used to collect data on participants’ knowledge, attitudes, and practices related to drug disposal. Insights from the survey informed the design of PillBin, a multilingual mobile and web-based platform that provides educational resources and interactive disposal guidance. Results: Awareness of official drug disposal guidelines was limited, while the commonest drug disposal method was found to be through the household trash. Awareness was higher among healthcare professionals. Most respondents expressed a need for additional information, with websites and mobile applications preferred as educational channels. Technology preferences did not differ by location. Analgesics, cough syrups, and antacids were the most commonly reported leftover medicines. Conclusion: The study highlights critical gaps in drug disposal awareness and practice in India, emphasizing the need for scalable solutions. PillBin addresses these gaps by offering accessible, multilingual digital education and disposal guidance, thereby contributing to safer pharmaceutical waste management and public health protection.
Keywords: Digital health intervention; Drug disposal; Health knowledge; Mobile application; Public health